Pancreatic Cancer Arising From the Remnant Pancreas: Is It a Local Recurrence or New Primary Lesion?. Issue 9 (October 2017) - Hashimoto, Daisuke; Chikamoto, Akira; Masuda, Toshiro; Nakagawa, Shigeki; Imai, Katsunori; Yamashita, Yo-ichi; Reber, Howard A.; Baba, Hideo
Abstract : Abstract: Local recurrence of pancreatic cancer (PC) can occur in the pancreatic remnant. In addition, new primary PC can develop in the remnant. There are limited data available regarding this so-called remnant PC. The aim of this review was to describe the characteristics and therapeutic strategy regarding remnant PC. A literature search was performed using Medline published in English according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines. The incidence of remnant PC has been reported to be 3% to 5%. It is difficult to distinguish local recurrence from new primary PC. Genetic diagnosis such as Kirsten rat sarcoma viral oncogene homolog mutation may resolve this problem. For patients with remnant PC, repeated pancreatectomy can be performed. Residual total pancreatectomy is the most common procedure. Recent studies have described the safety of the operation because of recent surgical progress and perioperative care. The patients with remnant PC without distant metastasis have shown good long-term outcomes, especially those who underwent repeated pancreatectomy. Adjuvant chemotherapy may contribute to longer survival. In conclusion, this review found that both local recurrence and new primary PC can develop in the pancreatic remnant. Repeated pancreatectomy for the remnant PC is a feasible procedure and can prolong patient survival.